Transformação digital na contabilidade: as novas competências do contador - Yugue, Marcelo (2022)
This research discusses the impact of digital transformation on corporate accounting departments. The research begins with the possible causes that accelerated the digital transformation in Brazilian corporations. In this path, it evaluates the importance of the impulse that the changes of the Secretariat of the Federal Revenue of Brazil produced in this evolution. Through the interdisciplinary propensity, it evaluates the interference of economy, technology and law in this transformation. Accounting science is a human science, so the study is also guided by the effects that these changes produce on the role played by the accountant. And it evaluates the new skills that the accountant needs to perform his new tasks. Finally, it outline the disruptive effects this accountant produces with his new weapons in the corporate environment, but not without discussing the precariousness in his fight for qualification